Between Como, Milan and Pavia: Female Religious Communities According to the Words of Margherita Lambertenghi (First Half of the 15th Century) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The essay presents a ‘memorial’ in vernacular, written in the 1440s to be used in the controversy between the monastery of S. Marta in Milan and the domus of S. Marco in Borgovico, near Como. The document, whose transcription is given at the end of the essay, was probably composed by Margherita Lambertenghi, who promoted the institutionalization of both monastries, and gives a precious and unusual point of view on the differentiated dynamics that supported the processes of institutionalization of forms of female religious life at the end of the Middle Ages.
Keywords: Female religious life; Monasteries; Church history; Vernacular